2018
DOI: 10.4274/tjh.2017.0372
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between baseline 18F-FDG PET/CT findings and CD38, CD138 expressing myeloma cells in bone marrow and clinical parameters in patiens with multiple myeloma

Abstract: ObjectiveThe aim of this study was to evaluate the relation between the rate of fluorine-18 (18F) fludeoxyglucose (FDG) uptake and CD38 and CD138 expression in myeloma cells in bone marrow and other clinical parameters in patients with multiple myeloma (MM).Materials and MethodsPatients with the diagnosis of MM who underwent 18F-FDG positron emission tomography/computed tomography (PET/CT) for initial staging were evaluated retrospectively. We analyzed a total of 42 patients (43-83 years old, mean: 64.4±9.9). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In another study, Cengiz et al reported that there was a significant correlation between bone marrow FDG uptake and percentage of CD38-and CD-138 expressing plasma cell. They also revealed the correlation between FDG uptake and some prognostically relevant laboratory parameters such as β2M and CRP [35]. As well the correlation between SUVmax in bone lesions and clinical parameters related to tumor burden such as high M protein, plasma cell >20% in bone marrow, β2M>3.5mg/dl, hypercalcemia at the onset of disease, and increased LDH was reported by Li et al [36].…”
Section: The Role Of Pet/ct In the Assessment Of Prognosismentioning
confidence: 56%
“…In another study, Cengiz et al reported that there was a significant correlation between bone marrow FDG uptake and percentage of CD38-and CD-138 expressing plasma cell. They also revealed the correlation between FDG uptake and some prognostically relevant laboratory parameters such as β2M and CRP [35]. As well the correlation between SUVmax in bone lesions and clinical parameters related to tumor burden such as high M protein, plasma cell >20% in bone marrow, β2M>3.5mg/dl, hypercalcemia at the onset of disease, and increased LDH was reported by Li et al [36].…”
Section: The Role Of Pet/ct In the Assessment Of Prognosismentioning
confidence: 56%
“…Previous studies reported a correlation between FDG uptake by BM and PC in ltration [12,20,28,29,[42][43][44][45], while others showed that FDG uptake correlated with b2m [28,29] and CRP (29) and negatively correlated with Hb and HT [29] as well as Alb [28].…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the semi-quantitative evaluation, the SUV max of the ROI, namely, the right anterior iliac crest, was calculated using semiautomatic image registration software package. The right anterior iliac crest was selected to standardize the calculation of FDG uptake by BM because it was the biopsy site and concordant with previous studies [12,28,29]. Figures 1 and 2 demonstrates the PET/CT scan image of MM patients.…”
Section: F-fdg Pet/ct Imagingmentioning
confidence: 88%
“…On the other hand, in the literature there are a few studies demonstrating a negative correlation between PET-CT parameters and HB. [ 30 , 31 ] However, those studies were conducted in patients with multiple myeloma. The negative correlations observed in these studies may be related to multiple myeloma itself.…”
Section: Discussionmentioning
confidence: 99%